A Coagulation-Related Gene-Based Prognostic Model for Invasive Ductal Carcinoma - Li, Jing; Du, Jiajia; Wang, Yanhong; Jia, Hongyan (Frontiers in Genetics, 2021)
Background: Invasive ductal carcinoma (IDC) is the most common type of metastatic breast cancer (BC). Due to the lack of molecular targets for IDC therapy, the further diagnosis of IDC remains a challenge. A large number of studies have confirmed that coagulation is positively correlated with angiogenesis-related factors in metastatic breast cancer. Methods: The 50 hallmark gene sets were obtained from GSEA database to conduct Gene Set Variation Analysis(GSVA). GEO database was used to identify differentially expressed HALLMARK_COAGULATION genes between Ductal carcinoma in situ and Invasive ductal carcinoma samples. GSEA was applied to analyze the enrichment of genes. Then, the IDC samples of the TCGA database were divided into a training set and a validation set (7:3). The univariate and multivariate Cox regression analyses and qRT-PCR experiments were performed to identify prognostic genes. The overall survival (OS) curve and 5-year receiver operating characteristic curve (ROC) were drawn in both training set and validation set. Finally, a nomogram was constructed to predict the 1-, 2-, 3-, 4- and 5-year survival rates of IDC patients. Results: The ‘HALLMARK_COAGULATION’ pathway was activated and COAGULATION-related genes were significantly enriched in the IDC samples. There was a significant difference in the clinicopathological parameters between the DCIS and IDC patients. Compared with DCIS, five genes (SERPINA1, CAPN2, HMGCS2, MMP7 and PLAT) were screened to construct the prognostic model. The high-risk group showed a significantly lower survival rate compared to the low-risk group both in the training set and validation set (P = 3.5943e-06 and P=0.014243). The risk score was an independent predictor of prognosis for IDC patients. A nomogram including risk score, pathological_stage and pathological_N provided a quantitative method for clinicians to predict the probability of 1-, 2-, 3-, 4- and 5-year survival. The results of decision curve analysis (DCA) also demonstrated that the nomogram had a high potential for clinical utility. Conclusion: Our study revealed ‘HALLMARK_COAGULATION’ gene sets considerably enriched in IDC patients. Furthermore, we established a COAGULATION-related gene signature and further analyzed its prognostic value for ICD patients, which provided a new understanding for evaluating the survival and prognosis of patients with IDC.